Analysis of Intra-Articular Injection of Triamcinolone Acetonide on Changes in The Quality of Life of Patients With Knee Osteoarthritis - Lestari, Dewi; Widowati, Galuh (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Knee osteoarthritis is the most common articular disease in developed countries that caused chronic disability and reduction of the quality of life in the elderly. Intra-articular (IA) injections are selected if other conservative therapies are ineffective. Purpose: This study aimed to measure the effect of IA injection of triamcinolone acetonide on the quality of life in knee osteoarthritis’s patients. Methods: This observational research was conducted in three steps: filling out questionnaires by patients, interviewing patients, and retrieving patients' data from medical records. The patients' quality of life scores measure before and 4 weeks after therapy, using the AIMS2-SF score, VAS EQ-5D-5L, and Indonesian EQ-5D-5L. The result will be declared statistically significant if p<0.05. Results: No statistically significant difference found in AIMS2-SF scores (p> 0.05) for Symptoms, Social, Occupational domains, and in VAS EQ-5D-5L (p> 0.05). A significant difference was found in AIMS2-SF scores for Physical, Emotional domains and in the EQ-5D-5l Score. Multivariate analysis showed that patients' characteristics and knee osteoarthritis disease did not affect the AIMS2-SF, EQ-5D-5L, and VAS score. Conclusion: IA injection of triamcinolone acetonide has a potential effect to increase the number of domains in the patient's quality of life after 4 weeks of therapy.